EMPOWERING COASTAL COMMUNITIES OF ACEH Besar THROUGH DIVERSIFICATION OF FISH JERK PRODUCTS AS ADDED VALUE TO THE USEFULNESS OF TRASH FISH - Muhammad; Ichsan Rusydi; Syamsul Rizal; Thaib Rizwan; Zulkarnain Jalil; Zulfan; Imelda Agustina (CV. Naskah Aceh, 2023)
This service activity is planned to be carried out in Aceh Regency with the objectives: (1) To determine the increase in the economic value of trash fish from the cracker diversification process; (2) Knowing the increase in nutritional value of crackers with the addition of trash fish ingredients; (3) Knowing that there is a reduction in fish waste in the Lhok Sedu Leupung area of ​​Aceh Besar from the process of diversifying trash fish products (4) Can utilize technology transfer for the community to optimize existing marine potential. In this way, job opportunities are created for the local community so that prosperity and prosperity can be realized. Several factors that support the sustainable use of water resources for processing businesses include processing production technology, social and cultural conditions of the community, availability of infrastructure and capital. Strengthening food security is something that must be done to face the free market.